VD_FINDINFO HC / 2014 / 66 vom 16. Januar 2014 - VD Tribunal cantonal (2014)
ACCIDENT DE LA CIRCULATION, ASSURANCE-ACCIDENTS PRIVÉE, CLAUSE INSOLITE, FAUTE GRAVE, DÉLIT, INTENTION | 14 al. 2 LCA, 33 LCA